Prevalence and Risk Factors of Cervicitis in Married Women in Shahroud, Northeast of Iran - Bahare Ameri; Moussa Abolhassani; Fatemeh Mehravar (Golestan University Of Medical Sciences, 2018)
Introduction: Mucopurulent cervicitis (MPC) is a clinical syndrome characterized by mucopurulent discharge from the cervix and other signs of inflammation. In this study, we evaluated the prevalence and risk factors of MPC in married women referred to health centers of Shahroud (northeast of Iran) in 2016. Methods: In this cross-sectional study, 346 married women aged ≥18 years were screened for MPC via clinical examination by a gynecologist. Logistic regression was used to evaluate association of sociodemographic, behavioral and sexual health related variables with prevalence of cervicitis. Results: Mean age of subjects was 31.5 years (range 14-69 years) and 121 (35%) subjects had MPC. In addition, 38.2% of the subjects were with less than a high school diploma and 72.8% were housekeeper. The mean (standard deviation) value of body mass index was 25.2 (4.3) Kg/m2 (range: 16.2-38.5 Kg/m2). Coital frequency per week (P=0.004) and method of delivery (P=0.02) were significantly associated with the prevalence of cervicitis. Conclusion: Our findings suggest that weekly coital frequency, method of delivery, vaginal discharge and history of genital herpes may be associated with the risk of cervicitis.